Design and Development of Biodegradable Microporous Polymeric Systems with enhanced Characteristics for Food Packaging Applications - Mohamed, Mona (AUC Knowledge Fountain, 2019)
The principle of breathable food packaging is providing the optimum number of holes to transfer sufficient amount of oxygen into the packaging headspace. In fact, most of the commercial breathable food packaging are made from non-biodegradable plastic materials. However, these polymers are well known by their negative environmental consequences. Therefore, in this research, polylactic acid (PLA) and polycaprolactone (PCL) were chosen as biodegradable polymers to design permeable food packaging. These bio-renewable polymers were utilized in many biomedical and food packaging applications because of their contribution to the environmental sustainability. In addition, sodium chloride (NaCl) and polyethylene oxide (PEO) were used to develop microporous films by solvent casting/leaching out technique. Thus, it was found through the experimental results that sodium chloride with composition of 50% and PEO with composition of 10% achieved the highest air permeability and oxygen transmission rate (O2TR) with PLA. Nevertheless, increasing in NaCl percentage showed lower air permeability compared with 50% because of the NaCl agglomeration and formation of larger pores. Indeed, this finding was proved by increasing is PLA crystallinity, which was associated with increasing in NaCl percentage. In addition, the same result was also demonstrated by increasing in the Brunauer-Emmett-Teller (BET) surface area and pores volume that were observed with increasing in NaCl composition. Moreover, incomplete extraction of agglomerated NaCl was another reason in the permeability reduction. Furthermore, the concentration of PEO was increased in order to improve the interconnectivity of the pores within PLA matrices. However, it was found that increasing in PEO percentage above 10% did not improve air permeability because it led to increase pore size polydisparity and it led to increase the tortuosity of the diffusion path within the polymeric matrices. However, increasing in the BET surface area of the porous PLA film was observed at 20 % PEO. According to these results, 50% NaCl and 10% PEO were chosen as optimum concentrations to further development in the properties of the porous films. Polylactic acid is characterized by stiffness and low elongation at break percentage. Therefore, PCL was added to PLA in order to improve its mechanical properties as a food packaging material. Hence, PLA was blended with different concentrations form PCL. In order to choose the optimum concentration of PCL, the mechanical properties for each blend was investigated. The result showed that the blend of 80% PCL and 20% PLA was characterized with the best mechanical properties in terms of elongation percentage at break and the maximum energy needed to break. Accordingly, the blend of 80% PCL and 20% PLA was chosen to study the effect of NaCl composition on the developed microporosity in the presence of PCL. In contrast to porous PLA films, the blend showed increasing in air permeability and O2TR when NaCl percentage increased. In fact, the highest air permeability and O2TR showed at 100 % NaCl. Thus, this result indicated high dispersion of NaCl particles within the polymeric matrices. Consequentiality, high composition of NaCl formed large number of small pores due to the lack of agglomerated particles. Moreover, complete leaching out of NaCl due to the hydrophobicity of PCL was another reason in improving high porosity with high NaCl composition. The same result was proved through the observed proportional relationship between NaCl percentage and BET surface area. Nevertheless, low number of small pores was observed in porous PCL-PLA films compared with porous PLA films. This observation was resulted from incomplete extraction of PEO from the blend during leaching out step due high affinity between the two polymers. This result was proved by several characterization methods such as FTIR and TGA analysis. Porous films were coated by cinnamaldehyde, as a natural antimicrobial ingredient, to eliminate passing of pathogens through the porous food packaging material. Hence, the result showed that cinnamaldehyde concentration, porosity and nature of polymer affected antimicrobial properties. With regard to the porosity, it showed enhancing effect on the antibacterial properties through increasing loading capacity of cinnamladehyade in the films. In addition, the result showed that PCL was more interactive with cinnamaldehyade than PLA because of PCL is more hydrophobic than PLA. Therefore, porous PCL-PLA films showed antibacterial effect at lower concentration of cinnamaldhyade than porous PLA films.